REFORMULATION OF INDONESIAN HOUSE OF REPRESENTATIVES TERM PERIOD RULES TO REALIZE LEGAL CERTAINTY AND JUSTICE - Banuoka, I Gede Adhi Maha Krisna; Yusa, I Gede (YURIS: Journal of Court and Justice, 2025)
The purpose of this paper is to examine and analyze the legal regulations regarding the term of office of the Indonesian House of Representatives and to examine and analyze the reformulation of the rules regarding the term of office of the Indonesian House of Representatives in realizing justice and legal certainty. This research is expected to provide benefits in the form of a legal understanding of the importance of clear regulations related to the limitation of the term of office of the House of Representatives and to contribute ideas in the field of Legal Science. The ambiguity of norms underlies this paper using normative legal research methods through a statutory approach and a comparative approach analyzed using descriptive, argumentative, and evaluative techniques. The results of the study indicate that Article 76 paragraph (4) of the MD3 Law stipulates that “The term of office of DPR members is 5 (five) years and ends when the new DPR members take the oath/promise.” From this article, it can be interpreted that although the term of office of the DPR has been clearly regulated for 5 years, the limit on how many times a person can be elected to the DPR is not expressly regulated so that it is necessaryReformulated to be “The term of office of DPR members is 5 (five) years and ends when the new DPR member takes the oath/promise and is only for two terms of office.” Or further regulated in paragraph (5) that “Each DPR member is limited to 2 terms of office.”In order to provide legal certainty, there are term limits for all high state institutions, thereby guaranteeing justice in fulfilling the constitutional rights of the people as a democratic nation.